Assessment of Fetal Gestational Age in Different Trimesters from Ultrasonographic Measurements of Biparietal Diameter in the Region of Udaipur - Hina Sharma; Dharamanjai Kumar Sharma; Ila Sharma (Academia Anatomica International, 2019)
Introduction: Precise estimation of gestational age is the key to proper antepartum care. Ultrasonographic estimation of fetal age using various fetal parameters is utilized for accurate estimation because estimation by last menstrual period is not reliable in all cases. Objectives: To assess gestational age with the help of ultrasonographic measurements of fetal biparietaldiameter in the local population of the region of Udaipur district of Rajasthan and thereby evaluate significance of this fetal biometric parameter in the prediction of gestational age by ultrasound. Subjects and Methods: Data of Ultrasonographic measurements and patient history was taken from the past records. Statistical analysis: Mean, standard deviation, statistical significance and t test were calculated. Results: The ultrasonographic measurement of biparietal diameter is a reliable indicator of gestational age in second and third trimesters. Conclusion: The derived gestational age is comparable with that used by Hadlock et al.